S67 Wnt11 Inhibits TGFb-Induced Epithelial-Mesenchymal Transition in a 3-Dimensional Human Lung Tissue Model. (19th November 2012) - Bartis, D; D'Souza, VK; Wang, Q; Pongracz, JE; Thickett, DR
Abstract : TGFβ1 has been implicated as a key effector in mediating Epithelial-Mesenchymal Transition (EMT), my ofibroblastic transdifferentiation and fibroproliferation in the fibrotic diseases of the lung. ATII cells show high differentiational plasticity: either transdifferentiation into ATI or a myofibroblastic phenotype might occur during the disease course. Factors regulating alveolar epithelial differentiation and EMT have high importance in lung regeneration therapy. The support of mesenchymal cells likely contributes to the homeostasis and regeneration of pulmonary epithelium. To study these mesenchymal effects, we constructed a 3-dimensional (3D) human tissue model of primary human ATIIs and pulmonary fibroblasts to mimic epithelial-mesenchymal interactions in the lung. ATII cells were obtained from lung cancer resection specimens from patients with normal lung function (n=10). ATII cells in the 3D model retain more differentiated epithelial phenotype compared to conventionally cultured cells (n=4). This is indicated by the higher expression levels of Aquaporin (AQP)3 (p=0.04) and AQP5 (p=0.19), Surfactant Protein (SP)-C (p=0.11) and E-cadherin. (p= 0.37) Cells cultured in 2D showed elevated markers of EMT over time whereas 3D cultured cells had significantly lower expression of mesenchymal markers N-cadherin (p<0.01), α-Smooth Muscle Actin (αSMA, p<0.01) and the transcription factor SLUG (p<0.01). This suggests that our co-culture model is more relevant in modelling lung diseases in vitro than monolayer epithelial cultures. We found that externally added recombinant Wnt11 (administered at 1µg/ml) inhibits phenotypic changes induced by TGFβ1 in 3D ATII+fibroblast co-cultures (n=6). Lung epithelial differentiation markers AQP3 (p=0.19), AQP5 (p=0.04), and SP-C (p=0.12) showed elevated expression levels upon the addition of Wnt11 to TGFβ1-treated cell cultures. Moreover, 1µg/ml Wnt11 blocked the EMT-inducing effects of 10ng/ml TGFβ1 in terms of the expression levels of SLUG (p=0.01), Vimentin (p<0.01) and αSMA (p=0.04). Our findings indicate that Wnt11 – which is naturally secreted by pulmonary cells - might contribute to the homeostasis and repair of epithelial cells. Our finding that the effects of TGFβ1 can be antagonised by Wnt11 may mark Wnt11 as a potential therapeutic target in fibrotic diseases of lung.